Bioestratinomic Classification and Genesis of Shell Beds (Coquinas) from the Santa Marta Formation (Upper Cretaceous) of James Ross Island, Antarctica - LUIZ CARLOS WEINSCHÜTZ; RENATO P. GHILARDI; ALEXANDER W.A. KELLNER; JULIANA M. SAYÃO (Anais da Academia Brasileira de Ciências)
Abstract Shell beds, or coquinas, have a complex origin, limiting their utility in paleoecology. However, such accumulations can serve as crucial paleoenvironmental indicators, since their bioestratinomic and diagenetic properties explain the physical-chemical and biological processes of their formation, as well as the ancient environments linked to their development. In 2016, the PALEOANTAR Project sampled coquinas from the James Ross Island (Antarctic Peninsula) in Passo São José (PSJ – San José Way) and Muro do Castelo (MDC – Castle Wall), two new localities with outcrops of the lower Lachman Crags Member, Santa Marta Formation, Marambio Group, Cretaceous of Larsen Basin. The paleontological content and sedimentary structures indicate a shallow marine depositional system. The PSJ coquina are composed by gastropods bioclasts, with predominantly dense/loose packing. The MDC presents a larger variety of bioclasts with bivalve dominance on a loose packing and conglomeratic horizons, that varies from granule to pebble. Sedimentary and biostratinomic features observed in samples from both localities indicate their genesis from high-energy events, characterized as a proximal tempestite. These descriptions allow a more accurate reconstruction of the depositional environments, highlighting the importance of these rocks in the geological record during the Cretaceous of Antarctica.